The remains of the day [videorecording (DVD)] - Ivory, James; Hopkins, Anthony, 1937-; Thompson, Emma; Ishiguro, Kazuo, 1954- (Columbia Tristar Home Entertainment, 2001)
The story of blind devotion and repressed love between a fanatically proper butler and a high-spirited, strong-minded young housekeeper employed by a British lord who is unwittingly a Nazi dupe.